SOCIAL LEADER DAN PERANNYA DALAM MENINGKATKAN MOTIVASI KERJA GURU (STUDI PADA SMPN 4 BATAGUH) - Noviani, Widy; Azizah, Nor; Madina, Maya; Aslamiah, Aslamiah; Cinantya, Celia (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to explore the best approach in improving teacher work motivation through the role of social leaders at SMP 4 Bataguh Kuala Kapuas Central Kalimantan. The methods used in this study are direct interviews, observations, and documentation studies. The principal of SMPN 4 Bataguh is the focus of this study. The methods used to test the collected data are (1) data reduction, (2) data presentation/display, and (3) verification or inference. The results of the study indicate that social leaders and their role in improving teacher work motivation can be started by providing an approach in the form of emotional and professional support so that teachers are more motivated. A social leader means someone who can communicate not only formally in front of many people, but also becomes a leader who can listen to what teachers need, support teacher performance/programs and others that certainly affect school progress. It is important for social leaders to promote a culture of appreciation and recognition in the school environment. Awards can be formal, such as awards for outstanding teachers, or informal, such as praise and daily recognition. The key to improving teacher work motivation through the role of social leaders is a human-centered approach